Security Management Using Planning Domain Definition Language: A Case For Ransomware Mitigation - Inayat, Afaq; Franco, Muriel F.; Scheid, Eder J.; Granville, Lisandro Z. (Anais da Escola Regional de Redes de Computadores (ERRC), 2023)
Network automation is essential for efficiently managing complex networks, enhancing reliability, and reducing human errors. This work proposes a novel approach to automate security planning and management using the Planning Domain Definition Language (PDDL). PDDL is used to generate an action plan to mitigate imminent threats to companies’ networks. The work demonstrates how PDDL can be applied to security planning in a dedicated scenario where there is a need to mitigate a ransomware attack targeting a company.